Aplicabilidade da inteligência artificial na subscrição de riscos dos contratos de resseguros internacionais - León, Gustavo Amado (2025)
Through this PhD thesis, we aim to explore the applicability of artificial intelligence as a tool for risk classification in international reinsurance contracts, contributing not only to the development of a solid theoretical foundation for International Law, Digital Law, and Insurance Law, but also by proposing practical solutions to the legal, regulatory, and ethical challenges associated with the topic. Furthermore, this research offers a unique opportunity to foster innovation within the legal framework specifically dedicated to international reinsurance contracts in the Digital Age, aligning such legal instruments with the demands of a market undergoing constant technological transformation. This approach will allow for a deeper understanding of the need to balance the interests of insurers, reinsurers, consumers, and the development of artificial intelligence itself, ensuring that its use in risk classification for international reinsurance contracts is safe, ethical, and legally compatible with the fundamental principles of Law. To that end, the structure adopted facilitates the reader’s comprehension of the academic work, which is divided into three chapters: the first dedicated to artificial intelligence, the second to the insurance and reinsurance sector, and the third to the applicability of artificial intelligence in the classification of risks in reinsurance contracts. Each chapter is further divided into subchapters to provide thematic clarity and precision. The first chapter offers a theoretical and historical foundation on artificial intelligence, beginning with the contributions of Alan Turing and the emergence of the information society, and culminating in the current dilemmas posed by the surveillance society. It addresses legal cybernetics as the intersection between law, technology and situates artificial intelligence within the framework of the Fourth Industrial Revolution, marked by the intensive use of robots, algorithms, machine learning, and deep learning. Wherever possible, these concepts are linked to the insurance sector and illustrated with examples from international reinsurance contracts, in order to contextualize the central theme. The chapter also examines the risks associated with artificial intelligence and the international efforts toward its regulation, emphasizing challenges such as transparency, algorithmic bias, and legal accountability. The second chapter outlines the technical and legal foundations of international reinsurance, beginning with the characterization of the insurance contract and its historical evolution. It then examines the contractual structure of reinsurance, international customs and practices, and key contractual clauses (including those related to claims, exclusions, and the so called SIC clauses), as well as the principles that govern reinsurance activity globally. This chapter also analyses the recent enactment of Law No. 15.040/2024 in Brazil, which introduces significant legal bases for the regulation of reinsurance activity in the country, with potential implications for contractual practices and adaptation to emerging technologies. The third chapter delves into the application of artificial intelligence in the risk classification process within reinsurance contracts. It analyses the impact of algorithmic decisionmaking, particularly in regard to risk profiling, pricing, and automated contractual exclusions. The chapter also addresses legal issues such as algorithmic discrimination, the right to privacy, and the extensive use of sensitive data, as well as the challenges the normative legal system faces in adapting to such innovations. Finally, it discusses the role of legal and regulatory coordination in Brazil and other jurisdictions, and presents a critical reflection on future scenarios for the use of artificial intelligence in the reinsurance sector, grounded in the harmonization of standards and international best practices. Although artificial intelligence is a widely discussed topic in the fields of technology and economics, few comprehensive studies have explored the interaction between artificial intelligence and reinsurance from a legal perspective. This represents a significant gap in academic knowledge that must be addressed, particularly in jurisdictions such as Brazil